Influence of synthesis conditions on carbonate entrapment in perovskite SrSnO(3) - Alves, Mary C. F.; Nascimento, Marcelo R.; Lima, Severino J. G.; Pizani, Paulo S.; Espinosa, Jose W. M.; Longo, Elson [UNESP]; Soledade, Luiz E. B.; Souza, Antonio G.; Santos, Ieda M. G. (Elsevier B.V., 2009)
Strontium stannate (SrSnO(3) a perovskite material, was synthesized by the polymeric precursor method, with different routes to eliminate organic matter. The utilization of pure oxygen for the elimination of organic matter changed the Raman spectra, especially in the low frequency region. Some peaks, which were previously assigned to the perovskite phase, were not noticed when the carbonate amount was lower. on the other hand, the profile of the IR spectra and XRD patterns did not change. These results suggest that carbonate may be present inside the perovskite lattice. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Strontium stannate; Pechini method; Perovskite